Visual criminology :new horizons in criminology - McClanahan, Bill (Book collections on Project MUSE., 2021)
In this pioneering work, Bill McClanahan provides a concise overview of visual criminology. With examples of the most prominent methods at work in visual criminology, this book explores the visual perspective in relation to prisons, police, the environment, and drugs, while noting the complex ethical implications embedded in visual research.